2021
DOI: 10.1042/bcj20200958
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the exposome to enable better ageing

Abstract: The sum total of life course exposures creates an exposome that has a significant impact on age-related health. Understanding the interplay between exposome factors and the (epi) genome, offers pertinent insights into the ageing process and its relationship with the accumulation of allostatic load. We propose to exploit this to develop a biomimetic approach that will provide insight into how evolution through natural selection in other species has solved many age related human health issues. In particular, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 80 publications
0
34
0
3
Order By: Relevance
“…Cumulative lifetime exposure to external stressors, such as temperature, oxygen levels and inadequate nutrition, elicit adaptive homeostatic mechanisms, including antioxidant and anti-inflammatory responses, by activating the NRF2–KEAP1 signalling pathway 274 . Modifying these exposures might offer new strategies for improving the health span and combatting CKD and could potentially have beneficial effects on cellular senescence.…”
Section: Interventions Targeting Senescencementioning
confidence: 99%
“…Cumulative lifetime exposure to external stressors, such as temperature, oxygen levels and inadequate nutrition, elicit adaptive homeostatic mechanisms, including antioxidant and anti-inflammatory responses, by activating the NRF2–KEAP1 signalling pathway 274 . Modifying these exposures might offer new strategies for improving the health span and combatting CKD and could potentially have beneficial effects on cellular senescence.…”
Section: Interventions Targeting Senescencementioning
confidence: 99%
“…Studies on cinnamon in vitro, in animals, and in humans are listed in Table 5 [9,45,[131][132][133][134][135][136][137][138][139][140][141][142][143][144]. Again, allowance for different exposome features, such as microbiota composition, may be pertinent here [145].…”
Section: Cinnamon and Cardiovascular Diseasementioning
confidence: 99%
“…Evidence from toxicology, comparative biology, and epidemiology demonstrate an association between environmental toxicant exposures and numerous age-related outcomes. Much of what we know about biological susceptibility to environmental toxicant exposure comes from children’s environmental health and is now being applied to other susceptible populations like the aged population ( Craven et al, 2021 ; Shiels et al, 2021 ). Exposure and response relationships can vary based on acute, short term or long-term exposures and are dependent on the chemical structure and physiological properties of toxicants.…”
Section: Aging Biology and Environmental Toxicantsmentioning
confidence: 99%
“…Diet quality is not only an important modifier of physiology, including gut microbiome composition which may affect detoxification. Diet is also often a source of toxicant exposure ( Roy et al, 2003 ; Wang et al, 2019 ) and has been shown to alter circadian rhythm homeostasis ( Gundert-Remy et al, 2015 ; Craven et al, 2021 ; Shiels et al, 2021 ). Diet is often linked with other lifestyle, behavioral or social factors that contribute to increased vulnerability to multiple sources of toxicants and social stressors simultaneously.…”
Section: Aging Biology and Environmental Toxicantsmentioning
confidence: 99%